2008
DOI: 10.1111/j.1753-318x.2008.00009.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of upland land management on flooding: insights from a multiscale experimental and modelling programme

Abstract: A programme of field experiments at the Pontbren catchment in Wales has, since autumn 2004, been examining the effects of land use change on flooding. The Pontbren catchment possesses a long history of artificial drainage of its clay soils and intensification of sheep farming. Increased flood runoff has been noted within the last decades, as has the mitigating effect of trees at field scale. To examine the local and catchment‐scale effects of land management within the catchment, including the potential advant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 26 publications
0
70
0
Order By: Relevance
“…While statistical methods have been able to identify catchmentscale effects of urbanisation (e.g. Institute of Hydrology (1999)), most of the knowledge on the effect of land use change on hydrological response comes from experimental catchment studies, and hydrological modelling (see among others Jackson et al, 2008); however, different results have been obtained, with some even opposing the findings of the others .…”
Section: Land Use Changementioning
confidence: 85%
“…While statistical methods have been able to identify catchmentscale effects of urbanisation (e.g. Institute of Hydrology (1999)), most of the knowledge on the effect of land use change on hydrological response comes from experimental catchment studies, and hydrological modelling (see among others Jackson et al, 2008); however, different results have been obtained, with some even opposing the findings of the others .…”
Section: Land Use Changementioning
confidence: 85%
“…Overgrazing is the cause of 23% of soil degradation in Europe (Royal Society for Nature Conservation, 1996). A recent study at Pontbren (Jackson et al, 2008a;Marshall et al, 2009) found that small tree strips on hillslopes have the potential to reduce peak flows by 40%, as the land is no longer trampled by livestock. Figure 2.5 demonstrates the impacts of heavy grazing on the soil structure and the hydrological cycle.…”
Section: Buffer Stripsmentioning
confidence: 99%
“…Evans (1996) found that a 50% increase in stock numbers coincided with a 25% increase in surface runoff in the Derwent catchment between 1944 and 1975. A modelling study by Jackson et al, (2008a) found that introducing tree shelterbelts with no grazing decreased overland flow by up to 60%, resulting in peak flows decreasing by between 10% and 40%. Another key hydrological storage zone is water on the floodplain and slopes.…”
Section: Effect Of Compaction On Hydrological Processesmentioning
confidence: 99%
See 2 more Smart Citations